The Strategy To Translate Metaphor - Yunita Widiyantari (UIN Salatiga, 2012)
Metaphor is called as part of comparison figure of speech. It compares two thing implisitly without using any comparison words such as, like, resemble to, etc. As a figurative expression, metaphor requires a special treatment to translate. The ability of the translator is very much influence to the result of metaphorical translation. He is not only have to empower himself with both source and target languages but also he better has a deep cultural understanding especially about metaphor. There are four types of metaphor on Ullmann version (1972: 213 - 216), namely: Antropomorfis etmaphor, animal metaphor, the abstract to concrete transfer and vise versa, sinaestetic metaphor. Furthermore, there are three criteria that should be fulfilled to value the quality of a translation viz the accuracy, the acceptability, and the text readability.Keywords: Translation; Strategy; Metaphor